A prospective randomised double-blinded study of intranasal midazolam atomizer spray for procedural sedation in paediatric patients - V., Vijaykumara; Nellore, Shalaka S.; Tendolkar, Bharati (International Journal of Research in Medical Sciences, 2016)
Background: Premedication prior to anaesthesia in children provides anxiolysis, facilitates parenteral separation and lessens adverse psychological effects on young minds. The present study was designed to study the safety, acceptability and degree of sedation by intranasal midazolam spray in children undergoing short procedures like endoscopy and CT scan. Methods: Sixty children scheduled for CT scan or endoscopy were randomly divided in to two groups. Thirty patients received intranasal midazolam spray 0.2 mg/kg, 20 minutes prior to procedure (group M) while other thirty patients received intra-nasal 0.9% normal saline spray (group C). Vital parameters such as heart rate (HR), systolic and diastolic blood pressure, respiratory rate (RR), SpO2, ramsay sedation score (RSS) and anxiety score level was observed and recorded prior to the premedication and then every 5 minutes till the end of the procedure. Parenteral separation and behaviour of the patient while entering the procedure room was also evaluated in both groups. Results: The mean heart rate, systolic blood pressure, respiratory rate, oxygen saturation were comparable between groups M and C. The mean diastolic blood pressure was significantly lower in group M as compared to group C. RSS and anxiety level score achieved were significantly higher in group M thereby facilitating easy parenteral separation. Conclusions: We can thereby say that administration of preservative free intranasal midazolam atomizer spray in dose of 0.2mg/kg as premedication in paediatric patients produces satisfactory level of sedation and anxiolysis with minimal adverse effects.